The veiled Garvey : the life & times of Amy Jacques Garvey - Taylor, Ula Y. (Chapel Hill : University of North Carolina Press, 2002)
In this biography, Ula Taylor explores the life and ideas of one of the most important, if largely unsung, Pan-African freedom fighters of the 20th century: Amy Jacques Garvey (1895-1973).
Formative years, 1895-1917 -- Amy Jacques and the UNIA -- I only live to perpetuate the ideas of my husband -- Our women and what they think -- Back to Jamaica and forward to Europe -- New freedoms, new constraints -- Single motherhood -- Decade of unity -- Fifth Pan-African Congress, 1945 -- Essays and literature for a Pan-African world -- Activism closer to home -- Progressive radical.
Includes bibliographical references (pages 281-295) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Garvey, Amy Jacques; Garvey, Marcus, -- 1887-1940.; Garvey, Amy Jacques; Garvey, Marcus, -- 1887-1940; Garvey, Amy Jacques -- 1895-1973; Garvey, Amy Jacques; Garvey, Amy Jacques; Garvey, Amy Jacques; Garvey, Marcus, -- 1887-1940; African American women political activists -- Biography; Political activists -- United States -- Biography; Feminists -- United States -- Biography; Women intellectuals -- United States -- Biography; Black nationalism -- United States -- History -- 20th century; Pan-Africanism -- History -- 20th century; African American women -- Political activity -- History -- 20th century; Feminism -- United States -- History -- 20th century; Femmes activistes noires américaines -- Biographies; Activistes -- États-Unis -- Biographies; Féministes -- États-Unis -- Biographies; Intellectuelles -- États-Unis -- Biographies; Nationalisme noir -- États-Unis -- Histoire -- 20e siècle.; Panafricanisme -- Histoire -- 20e siècle.; Noires américaines -- Activité politique -- Histoire -- 20e siècle.; Féminisme -- États-Unis -- Histoire -- 20e siècle.; BIOGRAPHY & AUTOBIOGRAPHY -- Social Scientists & Psychologists; SOCIAL SCIENCE -- Ethnic Studies -- African American Studies; African American women political activists; African American women -- Political activity; Black nationalism; Feminism; Feminists; Pan-Africanism; Political activists; Women intellectuals; United States; African American women political activists -- Biography; Political activists -- United States -- Biography; Feminists -- United States -- Biography; Women intellectuals -- United States -- Biography; Black nationalism -- United States -- History -- 20th century; Pan-Africanism -- History -- 20th century; African American women -- Political activity -- History -- 20th century; Feminism -- United States -- History -- 20th century; 1900-1999; Biography; Biographies; History; Biographies; Biographies